Ozone exposition in relation to vitality in a fir (Abies religiosa ( Kunth) Schltdl. & Cham) forest - González-Medina, Rebeca Eugenia; Mendoza-Briseño, Martín; Alvarado-Rosales, Dionicio (Instituto de Ecología, A.C., 2016)
Tropospheric ozone has been suspected to cause poor vitality and occasional massive mortality in sacred fir (Abies religiosa ( Kunth) Schltdl. & Cham) from Desierto de los Leones National Park, in Mexico City, Mexico, since 1980`s. This work searches for empirical evidences of ozone effects on health indicators of natural populations of sacred from August 2001 to January 2003. We monitored 31 selectively chosen sampling plots with passive monitors. Two additional fir forests with expected low exposure to ozone were used as control. Mean hourly ozone concentration per period (2 to 3 weeks each), fluctuated between 4,826 x10-7 and 0,0441 ppm. Most ozone readings were high, the mean hourly concentration in Desierto de Los Leones was 0,0186 ppm, but only three readings marginally exceeded a 0,0400 ppm toxic threshold. Ozone concentrations in control areas had a lower average (0 ,0145 ppm), with erratic wide fluctuations. We found no relationship between ozone concentrations and sampling plot location, elevation, temperature or region. Foliage retention, crown density, vigor and stand basal area follow weak, but constant and consistent worsening trends as ozone mean site concentration increases. This trend suggests fir health reduction with increasing ozone concentration; control values are consistent with this trend. This result differs from reports of ozone damages on fir, except the case of Switzerland where fir occurs at high elevations and shows clear anatomic damages due to chronic ozone exposure, just like the Mexican case.